Bilateral avulsion of the puborectal muscle: magnetic resonance imaging-based three-dimensional reconstruction and comparison with a model of a healthy nulliparous woman - Otcenasek, M; Krofta, L; Baca, V; Grill, R; Kucera, E; Herman, H; Vasicka, I; Drahonovsky, J; Feyereisl, J (Ultrasound in obstetrics & gynecology, 2007)
OBJECTIVES: Obstetric trauma to the puborectal muscle seems to be an important cause of pelvic floor dysfunction in women. Due to the complicated three-dimensional (3D) arrangement of the pelvic structures, two-dimensional images are not sufficient to demonstrate its relationships in a complex fashion. Thus, we aimed to create a 3D computer model to visualize the normal female pelvic floor anatomy and to compare this with the anatomy after bilateral avulsion of the puborectal muscle following delivery. METHODS: We created two 3D computer models of the female pelvic floor, one of a healthy nulliparous woman and the other of a woman with bilateral puborectal muscle avulsion after vaginal delivery. The data for the models were obtained from magnetic resonance imaging examinations and the following structures were depicted: pelvic bones, puborectal muscle, internal obturator muscle, urethra, urinary bladder, vagina and rectum. The models were compared. RESULTS: The models allowed us to demonstrate in three dimensions changes in the puborectal muscle after avulsion. Its relations to the bone, internal obturator muscle, perineal membrane and the deep part of the external anal sphincter were modeled and differences from the normal non-injured anatomy were demonstrated. Avulsion altered the support to the whole endopelvic fascia and destabilized both the anterior and the posterior vaginal walls. CONCLUSIONS: The use of 3D technology including modeling allows for the acquisition of new knowledge and aids in the understanding of both normal and pathological pelvic anatomy.
Keywords: Humans; stresová inkontinence moči; Pregnancy; Image Processing, Computer-Assisted; ženské pohlaví; Magnetic Resonance Imaging; Prolapse; prolaps; Female; pánevní dno; Muscle, Skeletal; Pelvic Floor; Urinary Incontinence, Stress; kosterní svaly; magnetická rezonanční tomografie; počítačové zpracování obrazu; těhotenství; lidé